Capital shortages and unemployment in OECD countries - Αλεξίου Κωνσταντίνος; Αργείτης Γεώργιος (SPOUDAI Journal of Economics and Business, 2003)
The unemployment performance of the OECD countries has dramatically deteriorated over the last three decades. Low investment is likely to have been one of the causes of this rise in unemployment. This paper aims at gaining an insight into the relationship between capital stock and employment. The conducted econometric analysis, provides certain results, underpinning our hypothesis and argues in favour of implementing a Keynesian type macroeconomic policy in the OECD area. JEL Classification: B22, E60